Stress-mediated increases in systemic and local epinephrine impair skin wound healing: potential new indication for beta blockers. - Raja K Sivamani; Christine E Pullar; Catherine G Manabat-Hidalgo; David M Rocke; Richard C Carlsen; David G Greenhalgh; R Rivkah Isseroff (PLoS Medicine)
Background Stress, both acute and chronic, can impair cutaneous wound repair, which has previously been mechanistically ascribed to stress-induced elevations of cortisol. Here we aimed to examine an alternate explanation that the stress-induced hormone epinephrine directly impairs keratinocyte motility and wound re-epithelialization. Burn wounds are examined as a prototype of a high-stress, high-epinephrine, wound environment. Because keratinocytes express the beta2-adrenergic receptor (beta2AR), another study objective was to determine whether beta2AR antagonists could block epinephrine effects on healing and improve wound repair. Methods and findings Migratory rates of normal human keratinocytes exposed to physiologically relevant levels of epinephrine were measured. To determine the role of the receptor, keratinocytes derived from animals in which the beta2AR had been genetically deleted were similarly examined. The rate of healing of burn wounds generated in excised human skin in high and low epinephrine environments was measured. We utilized an in vivo burn wound model in animals with implanted pumps to deliver beta2AR active drugs to study how these alter healing in vivo. Immunocytochemistry and immunoblotting were used to examine the up-regulation of catecholamine synthetic enzymes in burned tissue, and immunoassay for epinephrine determined the levels of this catecholamine in affected tissue and in the circulation. When epinephrine levels in the culture medium are elevated to the range found in burn-stressed animals, the migratory rate of both cultured human and murine keratinocytes is impaired (reduced by 76%, 95% confidence interval [CI] 56%-95% in humans, p < 0.001, and by 36%, 95% CI 24%-49% in mice, p = 0.001), and wound re-epithelialization in explanted burned human skin is delayed (by 23%, 95% CI 10%-36%, p = 0.001), as compared to cells or tissues incubated in medium without added epinephrine. This impairment is reversed by beta2AR antagonists, is absent in murine keratinocytes that are genetically depleted of the beta2AR, and is reproduced by incubation of keratinocytes with other beta2AR-specific agonists. Activation of the beta2AR in cultured keratinocytes signals the down-regulation of the AKT pathway, accompanied by a stabilization of the actin cytoskeleton and an increase in focal adhesion formation, resulting in a nonmigratory phenotype. Burn wound injury in excised human skin also rapidly up-regulates the intra-epithelial expression of the epinephrine synthesizing enzyme phenylethanolamine-N-methyltransferase, and tissue levels of epinephrine rise dramatically (15-fold) in the burn wounded tissue (values of epinephrine expressed as pg/ug protein +/- standard error of the mean: unburned control, 0.6 +/- 0.36; immediately postburn, 9.6 +/- 1.58; 2 h postburn, 3.1 +/- 1.08; 24 h post-burn, 6.7 +/- 0.94). Finally, using an animal burn wound model (20% body surface in mice), we found that systemic treatment with betaAR antagonists results in a significant increase (44%, 95% CI 27%-61%, p < 0.00000001) in the rate of burn wound re-epithelialization. Conclusions This work demonstrates an alternate pathway by which stress can impair healing: by stress-induced elevation of epinephrine levels resulting in activation of the keratinocyte beta2AR and the impairment of cell motility and wound re-epithelialization. Furthermore, since the burn wound locally generates epinephrine in response to wounding, epinephrine levels are locally, as well as systemically, elevated, and wound healing is impacted by these dual mechanisms. Treatment with beta adrenergic antagonists significantly improves the rate of burn wound re-epithelialization. This work suggests that specific beta2AR antagonists may be apt, near-term translational therapeutic targets for enhancing burn wound healing, and may provide a novel, low-cost, safe approach to improving skin wound repair in the stressed individual.